Pre‐ and postnatal exposure to secondhand tobacco smoke and body composition at 12 years: periods of susceptibility. Issue 8 (27th July 2022) - Mourino, Nerea; Pérez‐Ríos, Mónica; Yolton, Kimberly; Lanphear, Bruce P.; Chen, Aimin; Buckley, Jessie P.; Kalkwarf, Heidi J.; Cecil, Kim M.; Braun, Joseph M.
Abstract: Objective: The study aimed to identify periods of heightened susceptibility to the effects of pre‐ and postnatal secondhand tobacco smoke (SHS) exposure on body composition at age 12 years. Methods: The study used data from 217 children from the Health Outcomes and Measures of the Environment (HOME) Study, a prospective cohort in Cincinnati, Ohio. Using multiple informant models, the study estimated associations of maternal serum cotinine (16 and 26 weeks of pregnancy) and child serum cotinine concentrations (at age 12, 24, 36, and 48 months) with measures of body composition obtained with anthropometry and dual‐energy x‐ray absorptiometry at 12 years. We examined whether there were differences between these associations for pre‐ and postnatal exposure periods and potential effect measure modification by sex. Results: Postnatal cotinine concentrations were associated with higher weight, BMI, body fat and lean mass, waist circumference, and visceral, android, and gynoid fat. Each 10‐fold increase in postnatal cotinine was associated with 76% increased risk of overweight or obesity (95% CI: 1.13‐2.75). Associations between prenatal concentrations and measures of body composition at 12 years were generally null. Conclusions: Postnatal exposure to SHS may increase adolescent adiposity and lean mass. Future studies should determine whether early‐life exposures to SHS are associated with other cardiometabolic risk markers.